Cell cycle-targeting microRNAs promote differentiation by enforcing cell-cycle exit - Otto, Tobias (Proc Natl Acad Sci U S A, 2017)
MicroRNAs (miRNAs) have been known to affect various biological processes by repressing expression of specific genes. Here we describe an essential function of the miR-34/449 family during differentiation of epithelial cells. We found that miR-34/449 suppresses the cell-cycle machinery in vivo and promotes cell-cycle exit, thereby allowing epithelial cell differentiation. Constitutive ablation of all six members of this miRNA family causes derepression of multiple cell cycle-promoting proteins, thereby preventing epithelial cells from exiting the cell cycle and entering a quiescent state. As a result, formation of motile multicilia is strongly inhibited in several tissues such as the respiratory epithelium and the fallopian tube. Consequently, mice lacking miR-34/449 display infertility as well as severe chronic airway disease leading to postnatal death. These results demonstrate that miRNA-mediated repression of the cell cycle is required to allow epithelial cell differentiation.